Regional Inequalities in the Visegrad Group Countries, Serbia and Croatia - Klamár, Radoslav; Kozoň, Ján; Ivanová, Monika (Geographica Pannonica, 2020)
The paper discusses the evaluation of regional inequalities in the V4 countries, Serbia and Croatia. The gross birth rate, the unemployment rate, the average monthly gross earnings, the gross domestic product per capita and dwellings completed per 1000 inhabitants were selected as a set of evaluation indicators and, to determine the level of regional inequalities were used the Gini Coefficient and the Coefficient of Variation in two variants – in all the counties as well as after excluding the capital cities. Using the integrated indicator of the socio-economic status, the development of counties was evaluated as well as the dichotomy within the meaning of prosperous west vs. problematic east in the countries concerned. At the same time, we evaluated the degree of dependence between socio-economic status of the countries and the level of their regional inequalities involving the selected indicators.
Keywords: Croatia, regional inequalities, Serbia, socio-economic status, Visegrad Group countries, west-east dichotomy